WORDS AS “LEXICAL UNITS” IN LEARNING/TEACHING VOCABULARY - Almela, Moisés; Sánchez, Aquilino (International Journal of English Studies, 2009)
One of the genuine contributions of theoretical linguistics to the interdisciplinary field of applied linguistics is to elucidate the nature of what should be taught and how it should be taught. Traditionally, the input supplied in vocabulary teaching has consisted either of word lists (most often) or of words-in-context (more recently). In the first case, words are treated as self-contained receptacles of meaning, and in the second case, they are considered as nodes of semantic relationships. However, recent directions in corpus-driven lexicology are exploring the gulf between the concept of a “word” and that of a “semantic unit”. The main purpose of this paper is to update some implications of this discussion for one of the applied disciplines, namely FL/L2 vocabulary teaching and learning.